Decay of Trichomes of Arthrospira platensis After Permeabilization Through Pulsed Electric Fields (PEFs) Causes the Release of Phycocyanin - Knappert, Justus; Nolte, Jonas; Friese, Natalya; Yang, Ye; Lindenberger, Christoph; Rauh, Cornelia; McHardy, Christopher (Frontiers in Sustainable Food Systems, 2022)
The cyanobacterium Arthrospira platensis is a promising source for edible proteins and other high valuable substances such as the blue pigment-protein complex phycocyanin. The technology of Pulsed electric field (PEF) was recently studied to permeabilize the cell membrane, enhancing the mass transfer of water-soluble cell metabolites. Unfortunately, the question of the release mechanism is not sufficiently clarified in the published literature. In this work, the degree of cell permeabilization (cell disintegration index) was directly measured by means of a new method using the fluorescent dye propidium iodide (PI). The method allows conclusions to be drawn about the effects of treatment time, electric field strength and treatment temperature. Using a self-developed algorithm for image segmentation, the disintegration of trichomes was observed over a period of 3 hours. This revealed a direct correlation between the cell disintegration index and the decay of the trichomes. This decay, in turn, could be brought into a direct temporal relationship with the release of phycocyanin. The work shows for the first time the relation between permeabilization and the kinetics of particle decay and phycocyanin extraction and contributes to a deeper understanding regarding the release of cell metabolites in response to PEF. The results facilitate the design of downstream processes to produce sustainable products from Arthrospira platensis.